PTSD and DNA Methylation in Select Immune Function Gene Promoter Regions: A Repeated Measures Case-Control Study of U.S. Military Service Members - Rusiecki, Jennifer A.; Byrne, Celia; Galdzicki, Zygmunt; Srikantan, Vasantha; Chen, Ligong; Poulin, Matthew; Yan, Liying; Baccarelli, Andrea (Frontiers in Psychiatry, 2013)
Background The underlying molecular mechanisms of PTSD are largely unknown. Distinct expression signatures for PTSD have been found, in particular for immune activation transcripts. DNA methylation may be significant in the pathophysiology of PTSD, since the process is intrinsically linked to gene expression. We evaluated temporal changes in DNA methylation in select promoter regions of immune system-related genes in U.S. military service members with a PTSD diagnosis, pre- and post-diagnosis, and in controls. Methods Cases (n=75) had a post-deployment diagnosis of PTSD in their medical record. Controls (n=75) were randomly selected service members with no PTSD diagnosis. DNA was extracted from pre- and post-deployment sera. DNA methylation (%5-mC) was quantified at specific CpG sites in promoter regions of insulin-like growth factor 2 (IGF2), long non-coding RNA transcript H19, interleukin-8 (IL8), IL16, and IL18 via pyrosequencing. We used multivariate analysis of variance and generalized linear models to make temporal comparisons of %5-mC for cases (pre- to post-deployment) versus controls (pre- to post-deployment). Results: There were significant differences in the change of %5-mC pre- to post-deployment between cases and controls for H19 (p=0.04) and IL18 (p=0.01). For H19 the difference was driven by a significant reduction in %5-mC among controls. For IL18 the difference was driven by both a reduction in %5-mC among controls and an increase in %5-mC among cases. Conclusions: Patterns of reduced methylation of H19 and IL18 after deployment, a proxy of potential exposure to traumatic events, may indicate resilience to PTSD. Likewise, patterns of increased methylation after deployment of IL18 may indicate vulnerability to PTSD. These findings are preliminary and should be investigated in larger studies.